(untitled) (Journal of Enam Medical College, 2014)
Background: Diabetic ketoacidosis (DKA) is one of the most common acute complications of diabetes mellitus (DM). DKA is a recognised presenting feature of type 1 DM, but it commonly complicates previously diagnosed diabetic patients of all types, specially if they get infection or discontinue treatment. Objective: To describe the precipitating causes of DKA. Materials and Methods: This cross-sectional study was done from September to November, 2010 in Bangladesh Institute of Research & Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM). Diagnosed DKA cases were evaluated clinically and by laboratory investigations for identification of precipitating causes. Results: Out of 50 patients, 28 were female. Mean age was 38.3 years. Forty patients (80%) were known diabetics and 10 (20%) were detected diabetic first time during this admission. Severe DKA cases were less common. Infection (20, 40%) was the commonest precipitating cause followed by noncompliance (14, 28%). In 7 (14%) cases no cause could be identified. Other less common causes included acute myocardial infarction, acute pancreatitis, stroke and surgery. Conclusion: Infection and noncompliance were the major precipitants of DKA. So, it is assumed that many DKA cases might be prevented by proper counselling regarding adherence to medication and sick days management. DOI: http://dx.doi.org/10.3329/jemc.v4i2.19676 J Enam Med Col 2014; 4(2): 94-97